What does new classification of substance use disorders promise? - Mutlu, Elif (Journal of Dependence, 2016)
In the fifth edition of Diagnostic and Statistical Manual of Mental Disorders (DSM-5), one of the categories with substantial change is the chapter “Alcohol and Substance Related Disorders”. With the recent version, the terms “abuse” and “dependence” abolished to get replaced by the new criterion of “alcohol and substance use disorders”. How these new classifications and crite-rions will have an impact on the prevalence studies is still an issue of concern.